Technical analysis of improving the transmission efficiency of PCI-Express bus - Pan Jinlong; Li Dejian; Wang Yubo; Feng Xi; Dong Changzheng; Feng Wennan (Dianzi Jishu Yingyong)
The application scenarios of high-speed differential PCI Express bus are becoming wider and wider. In order to improve the efficiency of data transmission on the bus, this paper explains the bus structure, bandwidth overhead point and system parameter configuration of PCI-Express, and obtains the reasonable configuration to improve the bus transmission efficiency through the theoretical analysis and calculation of messages of different lengths under the background of read and write transmission. The PCI-Express bus transmission efficiency is significantly improved.